Pengaruh Kompensasi dan Motivasi terhadap Kinerja Karyawan Mitra Pengemudi Ojek Online Maxim Kota Pekalongan - Laxmi, Made Shania Puspa Ayu; Syarifuddin, Syarifuddin (eProceedings of Management, 2023)
This research is motivated by problems related to how companies can improve employee performance so that theycan support the success of achieving company goals. The problem is based onwith a decrease in employee performancewhich has an impact on company performance. One of the factors in the decline in performance is the lack ofcompensation and motivation provided by the company.This study aims to determine and analyze the effect ofcompensation and motivation on the performance of the Maxim Online Ojek Driver Partners in Pekalongan City. Theresearch method used in this research is quantitative method with descriptive-causality research type. Sampling wascarried out with non-probability sampling techniques used were:the sampling technique is saturated with the numberof respondents 56 respondents The results indicate that compensation (X1) and motivation (X2) simultaneously has asignificant positiv effect on employee performance (Y). This research is useful for Maxim Pekalongan to improveemployee performance through compensation and motivationKeywords-compensation, motivation, employee performance.